PROFIL LEMBAR KERJA SISWA BERBASIS LEARNING CYCLE 5-E MATERI BIOTEKNOLOGI - INDAH NURLATIFAH (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
This research aims to produce student worksheet in the base of Learning Cycle 5-E in biotechnology materials which is theoretically appropriate for learning process. The research designed by 4-D model. The developed student worksheet was tested on 15 students in 12th grade of SMA I Kediri. The instrument that is being used is validation sheet. Results showed that the developed student worksheet in the base of Learning Cycle 5-E is appropriate to be used. Based on content component, serving  component, language component and suitability component learning cycle 5-E model Keywords: Student worksheet, learning cycle 5-E, biotechnology